Legal and extra legal issues in journalism practice in Nigeria - Adams, Emmanuel Jibb; Ofordi , Joy Amarachi (Journal of Language, Literature, Social and Cultural Studies, 2024)
This research investigates the impediments faced by Nigerian journalists in upholding press freedom. Employing a mixed-methods approach that incorporates scholarly literature, legal documents, and media reports, the study identifies both legal and extra-legal challenges journalists encounter. Hinge on Libertarian Media Theory, these challenges include restrictive legislation, political influence, economic hardship, societal prejudices, safety concerns, self-censorship, and threats to media autonomy. Methodologically, the paper used a mixed-methods approach, combining analysis of scholarly literature, legal documents, and media reports with in-depth interviews with NUJ members. The interviews explored journalists' experiences with legal and extra-legal challenges, and the data were analyzed to identify themes. The research also explores the Nigerian Union of Journalists’ (NUJ) role in supporting journalists and press freedom. Findings from in-depth interviews with NUJ members reveal the significant impact of these constraints on media professionals. The study concludes with a call for increased engagement and proactive measures to address the systemic issues undermining press freedom in Nigeria. Among the recommendations, the research emphasizes the need for legislative reforms to revise or repeal outdated laws that restrict free expression. This effort should involve collaboration between government officials, legal experts, and civil society organizations to ensure alignment with international standards.